Analise de in vitro de substancias dessensibilizantes quanto ao potencial de obliteração de tubulos dentinários - Sartori, Carolina Oberg (2006)
The hypersensitivity dentine is clinically described as a painful response to thermic, chemical, mechanical, evaporative and osmotic stimuli on the dentinal tubules exposed to the buccal environment. The objective of the treatment to the dentine hypersensitivity is the pain remission by the obliteration of the dentinal tubules. The aim of this study was to assess different desensitizing substances concerning the obliteration potential of the dentinal tubules. 119 specimens obtained from bovine teeth were distributed in 8 groups: group 1- 10% strontium chloride gel (SCG- 10%), group 2- 2% sodium fluoride gel (SFG- 2%), group 3- 2% stannous fluoride gel (SnFG- 2%), group 4- 5% potassium nitrate gel (PNG- 5%), group 5- 10% potassium nitrate gel 10% (PNG- 10%), group 6- 3% potassium oxalate gel (POG- 3%), group 7- hydroxyethilcellulose gel (HEC), group 8- no treatment (NT). For the exposition of the dentinal tubules, it was used a 5mm deep carbide burr no. 245 and after that, it was applied 24% EDTA gel for 3 minutes. The samples were prepared for analysis with Scanning Electron Microscope (SEM), energy dispersive X ray (EDX) and microinfiltration with silver nitrate. The results with SEM showed that the groups treated by SCG- 10%, SFG- 2% and SnFG- 2% had open tubules. PNG- 5% and 10% showed partial tubules obliteration and deposits on the peritubular surface. The POG- 3% presented most of the tubules obliterated. In the analysis with EDX, it was possible to find all the main chemical elements of the formulations utilized, however, we observed just traces of the strontium, fluoride, sodium and potassium elements. The microinfiltration results presented significant differences (p<0.05) among agents, being the PNG- 10% (12.76±7.52μm), which presented the lowest value and the SCG- 10%, the biggest. It was concluded in this study that the 10% potassium nitrate showed a good potential obliteration of the dentinal tubules considering the methodology used. Key words: Hypersensitivity, Dentin, Desensitizing Substances